2017
DOI: 10.1111/dom.12971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight reduction on glycated haemoglobin in weight loss trials in patients with type 2 diabetes

Abstract: At group level, weight loss in obese and overweight patients with T2D was consistently accompanied by HbA1c reduction in a dose-dependent manner. The model developed in the present study estimates that for each kg of mean weight loss, there is a mean HbA1c reduction of 0.1 percentage points. HbA1c-lowering is greater in populations with poor glycaemic control than in well controlled populations with the same degree of weight loss. This summary of data from previous trials regarding the effect of weight reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 71 publications
(75 reference statements)
8
102
1
2
Order By: Relevance
“…This goes in sync with a research by Gummesson et al, which mentioned that weight loss in the overweight population is consistently associated with HbA1c, in a dose dependent manner. (Gummesson et al, 2017) We also found a reduction in the patients who were on these allopathic drugs. This indicates that CDC may be one of the factors associated with the decrease in load of medications in DM patients, and also helps them in avoiding the potential adverse effects of the allopathic medications.…”
Section: Resultssupporting
confidence: 54%
“…This goes in sync with a research by Gummesson et al, which mentioned that weight loss in the overweight population is consistently associated with HbA1c, in a dose dependent manner. (Gummesson et al, 2017) We also found a reduction in the patients who were on these allopathic drugs. This indicates that CDC may be one of the factors associated with the decrease in load of medications in DM patients, and also helps them in avoiding the potential adverse effects of the allopathic medications.…”
Section: Resultssupporting
confidence: 54%
“…Weight loss can lead to a reduction in obesity‐related complications, including the risk of developing diabetes . In overweight (body mass index [BMI] ≥25 kg/m 2 and <30 kg/m 2 ) or obese people (BMI ≥30 kg/m 2 ) who have progressed to type 2 diabetes (T2D), weight loss is associated with reductions in glycated haemoglobin (HbA1c), improvements in CVD risk factors and reductions in mortality …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In overweight (body mass index [BMI] ≥25 kg/m 2 and-<30 kg/m 2 ) or obese people (BMI ≥30 kg/m 2 ) who have progressed to type 2 diabetes (T2D), weight loss is associated with reductions in glycated haemoglobin (HbA1c), improvements in CVD risk factors and reductions in mortality. [8][9][10] Weight reduction through lifestyle interventions alone can be challenging. 11 Options for effective pharmacological treatments are limited, and those available require daily dosing.…”
Section: Introductionmentioning
confidence: 99%
“…Снижение массы тела сопровождается повышением чувствительности тканей к инсулину, улучшением метаболизма липидов, устранением латентного воспаления и, соответственно, играет важнейшую роль в профилактике СД2 и снижении риска его осложнений. Как показал математический анализ консервативных методов веде-ния больных СД2, каждый 1 кг снижения массы тела сопровождается уменьшением HbA 1c на 0,1% [10].…”
Section: оригинальная работаunclassified